(untitled) (The Planet, 2021)
Background: Pediatric dermatoses account for a higher proportion of outpatient department. Pediatric dermatoses are the common health problems seen in the developing countries. Objective: The purpose of present study was to find out the pattern of skin diseases among Pediatric Patient attending in OPD of Dermatology and Venereology, Sher-E-Bangla Medical College Hospital, Barishal, Bangladesh. Methods and Materials: This cross-sectional study was conducted in the outpatient department of Dermatology and Venereology, Sher-EBangla Medical College Hospital, Barishal, Bangladesh, during the period of 1st January 2017 to 31 December 2017. During study period total 29985 new patients visited skin VD OPD, for skin diseases. Among them 5998 patient Aged 1 day to 12 years were included in this study. All new diagnosed cases Aged 1 day to 12 years of both sex selected as study population. Diagnosis was done on clinical grounds and laboratory investigations were done whenever required. Observation: The Pattern of Pediatric Skin Diseases was higher in male 3129 (52.15%), than in female 2869 (47.85%). The most common dermatoses seen is Parasitic infection (31.08%), mostly scabies followed by bacterial infection (21.11%), fungal infection (18.18%), eczema (13.1%), viral infection (4.11%), urticaria (6.81%), vitiligo (.95%), psoriaris (.7%), drug reaction (.55%), acne (.45%), genodermatoses (.4%), neoplastic skin disorder (.3%) and others (2.23%). Conclusion: This study we found that common skin diseases of pediatric patient were Infective skin diseases mostly parasitic, bacterial and fungal are predominant in Bangladesh, though it is less frequent in developed countries.